Flame-retardant heat-insulating layer-shaped composite fabric and preparation method thereof

By combining surface-modified cotton fibers and phase-change microcapsules, combining soybean fibers, modified aramid 1313 fibers and polytetrafluoroethylene fibers, and using modified aerogels and polyurethane adhesives, flame-retardant and thermal insulation layered composite fabrics with excellent flame-retardant, heat-insulating, antistatic, and antibacterial properties are prepared, which solves the problem of insufficient performance of existing fabrics.

CN119590043AActive Publication Date: 2025-03-11ANHUI YIBEIYA TEXTILE CO LTD

Patent Information

Application Number
CN202411769796.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-11
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

The flame-retardant polyester fabrics have insufficient flame-retardant thermal insulation performance, and lack of antistatic and antibacterial properties, which limits its application range.

Method used

The cotton fibers were treated with sodium periodate and a modified mixture to prepare surface modified cotton fibers, and phase-changing microcapsules were prepared using ethyl cellulose and coconut oil as raw materials, and attached to the modified cotton fibers. Then, soybean fiber, modified cotton fiber and carbon fiber are blended into inner layer fabric, modified aramid fiber, cotton fiber and polytetrafluoroethylene fiber are blended into outer layer fabric, and flame-retardant and heat-insulating composite fabric is formed through modified aerogel treatment and the use of polyurethane adhesive.

Benefits of technology

It realizes the efficient flame-retardant, heat-insulating, anti-static, anti-bacterial, corrosion-resistant and water-repellent-repellent properties of flame-retardant and thermally insulated layered composite fabrics, which enhances its application potential in high-temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119590043A_ABST
    Figure CN119590043A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of layered materials, and discloses a flame-retardant heat-insulating layer-shaped composite fabric and a preparation method thereof. The preparation method of the flame-retardant heat-insulating layer-shaped composite fabric comprises the following steps: blending soybean fibers, modified cotton fibers and carbon fibers into yarns, and weaving to obtain a lining fabric; blending the modified aramid 1313 fiber, the cotton fiber and the polytetrafluoroethylene fiber into yarns, and weaving to obtain an outer-layer fabric; immersing the outer-layer fabric into the modified aerogel treating agent to obtain a functionalized outer-layer fabric; one side of the functionalized outer-layer fabric is coated with a polyurethane adhesive, the functionalized outer-layer fabric is attached to the inner-layer fabric, hot pressing is conducted, and the flame-retardant and heat-insulating layer-shaped composite fabric is obtained. The flame-retardant and heat-insulating layer-shaped composite fabric has excellent flame-retardant and heat-insulating properties and also has good antistatic property, antibacterial property, corrosion resistance, water and oil repellency, moisture absorption, breathability and skin friendliness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of layered materials, in particular to a flame retardant and heat insulating layered composite fabric and a preparation method thereof. Background Art

[0002] There are many kinds of fabrics for clothing on the market. Due to different usage scenarios, there are also different requirements for the functions of fabrics. Flame-retardant and heat-insulating fabrics have broad application prospects in production and life. For example, in life, flame-retardant and heat-insulating fabrics can be processed into heat-insulating gloves. In industrial production, flame-retardant and heat-insulating fabrics can be used in high-temperature environments in semiconductors, biopharmaceuticals, optical instruments, food and other industries. For example, Chinese patent application CN116353159A provides a flame-retardant polyester fabric, including a polyester fabric layer and a flame-retardant composite layer, wherein the flame-retardant composite layer includes a flame-retardant layer, a carbon layer and a heat-insulating layer, wherein the flame-retardant layer is a polyurethane flame-retardant layer, the carbon layer is a lignin gel layer, and the heat-insulating layer is an electrostatic spinning layer containing silica nanospheres. However, the flame-retardant and heat-insulating properties of the flame-retardant polyester fabric still need to be improved. At the same time, the lack of antistatic and antibacterial properties also limits the use of the flame-retardant polyester fabric. Summary of the invention

[0003] In order to solve the above technical problems, the present invention provides a method for preparing a flame retardant and heat insulating layered composite fabric, comprising the following steps:

[0004] Step (1), the cotton fiber is treated with a sodium periodate aqueous solution and a modified mixed solution containing 2-amino-2-hydroxy-1,1'-binaphthalene in sequence to obtain a surface-modified cotton fiber;

[0005] Step (2), using ethyl cellulose and coconut oil as raw materials to prepare phase change microcapsules; using citric acid as a crosslinking agent, connecting the phase change microcapsules to the surface modified cotton fibers to obtain modified cotton fibers;

[0006] Step (3), blending soybean fiber, modified cotton fiber and carbon fiber into yarn, weaving to obtain inner layer fabric; blending modified aramid 1313 fiber, cotton fiber and polytetrafluoroethylene fiber into yarn, weaving to obtain outer layer fabric;

[0007] The preparation method of modified aramid 1313 fiber comprises the following steps:

[0008] Step A1, tetraethylenepentamine reacts with methyl acrylate to obtain a polyamino polymer;

[0009] Step A2, pre-treating the aramid 1313 fiber to obtain the pre-treated aramid 1313 fiber; the pre-treated aramid 1313 fiber is treated with a polyamino polymer mixed solution, a silver nitrate aqueous solution, and steam to obtain a modified aramid 1313 fiber;

[0010] Step (4), immersing the outer fabric in a modified aerogel treatment agent for infiltration treatment to obtain a functional outer fabric; coating one side of the functional outer fabric with a polyurethane adhesive, laminating it with the inner fabric, and hot pressing it to obtain a flame retardant and heat insulating layered composite fabric;

[0011] The method for preparing the modified aerogel comprises the following steps:

[0012] Step B1, boric acid reacts with vinyltrimethoxysilane to obtain boron-doped silane; para-ester, 4-mercaptobenzaldehyde, and DOPO react to obtain a flame retardant modifier;

[0013] Step B2, extracting hemp fiber from hemp stems, and then cross-linking with chitosan and boron-doped silane to prepare aerogel powder;

[0014] Step B3: modifying the aerogel powder with a flame retardant modifier to obtain modified aerogel.

[0015] Preferably, in step (1), the preparation method of the surface modified cotton fiber is:

[0016] In a nitrogen atmosphere, under stirring conditions of 150-250 r / min, the cotton fiber is mixed with a sodium periodate aqueous solution having a concentration of 0.02 g / mL in a mass ratio of 1:(40-60), reacted at 30-40° C. in the dark for 1.5-2.5 h, filtered, washed, and dried to obtain pretreated cotton fiber;

[0017] The pretreated cotton fiber and the modified mixed solution are mixed in a mass ratio of 1:(40-60), reacted at 58-63°C for 3-4h, filtered, washed, and dried to obtain surface-modified cotton fiber; wherein the modified mixed solution is obtained by mixing 2-amino-2-hydroxy-1,1'-binaphthalene and methanol in a mass ratio of (2.8-5.6):(80-100) and ultrasonically treating for 10-20min;

[0018] In the above process, after the cotton fiber is oxidized by sodium periodate, part of the hydroxyl groups on the surface are converted into aldehyde groups, which then react with the amino groups of 2-amino-2-hydroxy-1,1'-binaphthalene to produce a Schiff base reaction, thereby introducing a binaphthyl structure with heat insulation and cooling capabilities on the surface of the cotton fiber.

[0019] Preferably, in step (2), the preparation method of the modified cotton fiber is:

[0020] Heat the coconut oil at 50-60°C for 5-10 minutes to melt, then mix it with a 1wt% polyvinyl alcohol aqueous solution, stir it at a speed of 1400-1600r / min for 10-20min, then add a 18.6wt% ethyl cellulose / acetone solution dropwise at a speed of 1-1.5mL / min, and stir it at a speed of 800-1000r / min for 2-3h at 32-38°C to obtain phase change microcapsules; wherein the mass ratio of coconut oil, polyvinyl alcohol aqueous solution, and ethyl cellulose / acetone solution is (5-10):(5-10):(15-40);

[0021] Add phase change microcapsules into deionized water, perform ultrasonic treatment for 10-20 minutes, add surface modified cotton fibers, stir for 10-20 minutes, then add citric acid and sodium hypophosphite, heat to 95-105°C at a heating rate of 1.5-2.5°C / min and maintain for 100-150 minutes, filter, wash, and dry to obtain modified cotton fibers; wherein the mass ratio of phase change microcapsules, deionized water, surface modified cotton fibers, citric acid, and sodium hypophosphite is (2-3):300:(10-15):(6-10):(6-10);

[0022] In the above process, phase change microcapsules with coconut oil as the phase change core material and ethyl cellulose as the shell were prepared by the evaporation solvent method. Furthermore, using citric acid as a cross-linking agent, the phase change microcapsules were grafted onto cotton fibers through an esterification reaction to obtain modified cotton fibers.

[0023] Preferably, in step (3), the mass ratio of the soybean fiber, modified cotton fiber and carbon fiber is (25-45):(56-76):(1-2), the yarn blended from them has an English count of 40-60S, and the gram weight of the inner layer fabric is 120-140g / m 2 .

[0024] Preferably, in step (3), the mass ratio of the modified aramid 1313 fiber, cotton fiber, and polytetrafluoroethylene fiber is (30-40):(20-30):(30-40), the English count of the yarn blended from them is 40-60S, and the gram weight of the outer fabric is 140-160g / m 2 .

[0025] Furthermore, in step (3), the method for preparing the modified aramid 1313 fiber comprises the following steps:

[0026] Step A1, in a nitrogen atmosphere, tetraethylene pentamine is placed in an ice water bath, and a 34.2wt% methyl acrylate / methanol solution is added dropwise at a rate of 0.8-1.2mL / min under stirring conditions. After the addition is completed, stirring is continued at room temperature for 3.5-4.5h, the temperature is raised to 145-155°C, and the mixture is allowed to stand for 3.5-4.5h to obtain a polyamino polymer; wherein the amount ratio of tetraethylene pentamine to methyl acrylate / methanol solution is (4.7-9.4)g:(7-14)mL;

[0027] In the above process, tetraethylenepentamine and methyl acrylate undergo Michael addition reaction and melt polycondensation to obtain a polyamino polymer;

[0028] Step A2, adding the washed aramid 1313 fiber to dichloromethane at a solid-liquid ratio of 4:(220-280), taking out after ultrasonic treatment for 20-40 minutes, then adding it to an epichlorohydrin treatment solution at a solid-liquid ratio of 4:(240-260), treating it at 38-42° C. for 100-150 minutes, taking it out, washing it with deionized water and acetone until the pH of the washing solution is 7, finally treating it with a sodium hydroxide aqueous solution with a mass fraction of 30-50wt% at 75-85° C. for 100-150 minutes, taking it out, and drying it to obtain pretreated aramid 1313 fiber; wherein the epichlorohydrin treatment solution is obtained by mixing epichlorohydrin and aluminum chloride at a mass ratio of 40:25;

[0029] Adding a polyamino polymer to deionized water to form a polyamino polymer mixed solution with a concentration of 0.5-2 g / L, adding the pretreated aramid 1313 fiber to the polyamino polymer mixed solution at a solid-liquid ratio of 1:(40-60), treating at 75-85° C. for 22-26 hours, taking out, washing, and drying to obtain surface-modified aramid 1313 fiber; adding the surface-modified aramid 1313 fiber to a silver nitrate aqueous solution with a concentration of 0.1-0.3 mol / L at a solid-liquid ratio of 1:(25-35), soaking for 50-70 minutes, and then subjecting the fiber to a steam treatment at 100° C. for 20-40 minutes, washing, and drying to obtain modified aramid 1313 fiber;

[0030] In the above process, epoxy groups are introduced on the surface of aramid 1313 fiber through Friedel-Crafts alkylation reaction, and the epoxy groups are then ring-opened to react with the amino groups of the polyamino polymer, so that the polyamino polymer is grafted onto the aramid 1313 fiber. Furthermore, the abundant amino groups and terminal primary amino groups in the polyamino polymer can effectively complex silver ions. Under hot steam conditions, part of the silver ions are reduced by the amino groups to form nanosilver and can effectively prevent the aggregation of nanosilver. The amino polymer plays a dual role of complexing agent and reducing agent.

[0031] Preferably, in step (4), the modified aerogel treatment agent is made of 1-3% (owf) modified aerogel and 10g / L sodium carbonate aqueous solution; the infiltration treatment conditions are: the bath ratio of the outer fabric to the modified aerogel treatment agent is 1: (15-25), and the infiltration treatment time is 50-100min; the rolling rate is 80%, first drying at 60-70°C, and then baking at 140-150°C for 3-5min;

[0032] In the above process, the H atom on the α-carbon in the para-ester structure introduced on the surface of the modified aerogel becomes active under alkaline conditions under the electron-withdrawing effect of the sulfonic group, and is easily eliminated to form a vinyl sulfonic group, which undergoes a covalent bonding reaction with the hydroxyl group on the cotton fiber in the outer fabric under alkaline conditions, thereby grafting the modified aerogel onto the outer fabric.

[0033] Preferably, in step (4), the coating amount of the polyurethane adhesive is 18-22 g / m 2 ; Hot pressing conditions: hot pressing for 20-40s at a pressure of 0.15-0.2MPa and a temperature of 100-110°C.

[0034] Furthermore, in step (4), the method for preparing the modified aerogel comprises the following steps:

[0035] Step B1, ethanol, a 37.5wt% hydrochloric acid aqueous solution, and vinyltrimethoxysilane are mixed, heated to reflux and stirred for reaction for 20-24h, and then the temperature of the mixed system is maintained at 65-75°C, and then boric acid is added, stirred for reaction for 2-3h, the temperature is raised to 80-85°C, and the stirring reaction is continued for 3-4h to obtain boron-doped silane; wherein the mass ratio of ethanol, hydrochloric acid aqueous solution, vinyltrimethoxysilane, and boric acid is (8.6-17.2):(19.9-39.8):(0.7-1.4):(0.9-1.8);

[0036] In the above process, vinyltrimethoxysilane is hydrolyzed to form silanol, which condenses with the hydroxyl group of boric acid to form boron-doped silane;

[0037] Step B2, cutting the hemp stems from which the bast has been stripped into pieces of 1-4 cm, crushing, soaking in deionized water for 10-15 hours, and then stirring with a 1 mol / L sodium hydroxide aqueous solution at 70-80° C. for 2-4 hours, and finally stirring with a 2 wt % sodium hypochlorite aqueous solution at 60-70° C. for 2-4 hours, filtering, washing, and freeze-drying to obtain hemp fibers;

[0038] A chitosan / acetic acid solution with a mass fraction of 0.1wt% and a boron-doped silane aqueous solution with a mass fraction of 1wt% are mixed, hemp fiber is added, ultrasonic treatment is performed, and then freeze-dried at (-80)-(-75)°C and ground to obtain an aerogel powder; wherein the mass ratio of the chitosan acetic acid solution, the boron-doped silane aqueous solution, and the hemp fiber is 100:(2-6):(0.003-0.005);

[0039] In the above process, chitosan, boron-doped silane, and hemp fiber are cross-linked to form an aerogel containing flame-retardant boron elements, and the aerogel structure contains abundant amino groups, hydroxyl groups, and carbon-carbon double bonds;

[0040] Step B3, adding the para-ester and 4-mercaptobenzaldehyde to dimethyl sulfoxide, ultrasonically treating at 40-45°C for 40-60min, then heating to 60-70°C for reaction for 3-4h, adding DOPO, heating to 80-90°C for further reaction for 4-5h, cooling to room temperature, centrifuging, washing, and drying to obtain a flame retardant modifier; wherein the mass ratio of the para-ester, 4-mercaptobenzaldehyde, dimethyl sulfoxide, and DOPO is (14-28):(6.9-13.8):(500-600):(10.8-21.6);

[0041] In the above process, the amino group of the para-ester reacts with the aldehyde group of 4-mercaptobenzaldehyde to form a C=N bond, and the C=N bond then adds with the active hydrogen of DOPO to form a flame retardant modifier containing nitrogen and phosphorus elements, and the flame retardant modifier contains a mercapto group and a para-ester structure;

[0042] The aerogel powder is added to N,N-dimethylformamide, ultrasonically dispersed for 20-40 minutes, heated to 50-80°C, and then a flame retardant modifier and azobisisobutyronitrile are added, stirred for reaction for 3-5 hours, and after the reaction is completed, centrifuged, washed, and dried to obtain a modified aerogel; wherein the mass ratio of aerogel powder, N,N-dimethylformamide, flame retardant modifier, and azobisisobutyronitrile is (3-5):(120-150):(1-1.5):(0.2-0.3);

[0043] In the above process, the carbon-carbon double bonds on the surface of the aerogel are combined with the thiol groups in the flame retardant modifier through a thiol-ene click reaction to obtain a modified aerogel.

[0044] The flame retardant and heat insulating layered composite fabric is prepared by the method for preparing the flame retardant and heat insulating layered composite fabric.

[0045] Compared with the prior art, the present invention has the following beneficial effects:

[0046] The flame-retardant and heat-insulating layered composite fabric of the present invention is composited by a functional outer layer fabric and an inner layer fabric. The functional outer layer fabric of the flame-retardant and heat-insulating layered composite fabric is made of modified aramid 1313 fiber, cotton fiber, and polytetrafluoroethylene fiber in a specific ratio and treated with a modified aerogel treatment agent. The aramid 1313 fiber has excellent flame retardancy, but due to its extremely strong fluffiness, it is easy to generate static electricity during the spinning process. Through the modification treatment, nanosilver is deposited in situ on its surface, so that the aramid 1313 fiber has antistatic and antibacterial properties, reducing the processing difficulty during the spinning process, and making the outer layer fabric have lasting antistatic and antibacterial properties; polytetrafluoroethylene Ethylene fiber has excellent high temperature resistance, chemical corrosion resistance and water and oil repellency, so that the outer layer of the fabric has permanent water and oil repellency and corrosion resistance; after the outer layer of the fabric is treated with a modified aerogel treatment agent, the modified aerogel is loaded on its surface in the form of a covalent bond. The porous network characteristics of the aerogel give it excellent thermal insulation properties, and the three elements of nitrogen, phosphorus and boron in the modified aerogel work synergistically to exert a significant flame retardant effect; therefore, the functionalized outer layer of the fabric has excellent flame retardant and heat insulation properties, antistatic properties, antibacterial properties, corrosion resistance and water and oil repellency.

[0047] The inner layer fabric of the flame-retardant and heat-insulating layered composite fabric is made of soybean fiber, modified cotton fiber and carbon fiber in a specific proportion. The soybean fiber has a soft feel like cashmere, and is superior to cotton in warmth retention and good skin-friendliness. The addition of carbon fiber helps to improve the antistatic properties of the inner layer fabric. The cotton fiber has good skin-friendliness and moisture absorption and air permeability. After modification, a binaphthyl structure and phase change microcapsules with heat insulation and cooling capabilities are introduced on its surface, which can better absorb the waste heat that penetrates the fabric. Therefore, the inner layer fabric has good thermal insulation, antistatic, moisture absorption, breathability and skin-friendliness.

[0048] In summary, the flame retardant and heat insulating layered composite fabric formed by the inner layer fabric and the functional outer layer fabric of the present invention not only has excellent flame retardant and heat insulating properties, but also has good antistatic properties, antibacterial properties, corrosion resistance, water and oil repellency, moisture absorption and air permeability, and skin-friendliness. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 It is a process flow chart of the preparation method of the flame retardant and heat insulating layered composite fabric of the present invention;

[0050] Figure 2 It is a comparison chart of limiting oxygen index test of flame retardant and heat insulating layered composite fabrics prepared in Example 3-5 of the present invention and Comparative Example 3-9;

[0051] Figure 3 It is a comparison chart of the Crowe value test of the flame retardant and heat insulating layered composite fabrics prepared in Examples 3-5 of the present invention and Comparative Examples 3-9. DETAILED DESCRIPTION

[0052] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0053] Example 1

[0054] This embodiment discloses a method for preparing modified aramid 1313 fiber, comprising the following steps:

[0055] Step A1, in a nitrogen atmosphere, place 7.1 g of tetraethylenepentamine in an ice-water bath, and add 10.5 mL of a 34.2 wt% methyl acrylate / methanol solution dropwise at a rate of 1 mL / min under stirring. After the addition is complete, continue stirring at room temperature for 4 h, heat to 150° C., and stand for 4 h to obtain a polyamino polymer;

[0056] Step A2, adding the washed aramid 1313 fiber to dichloromethane at a solid-liquid ratio of 4:250, taking it out after ultrasonic treatment for 30 minutes, then adding it to an epichlorohydrin treatment solution at a solid-liquid ratio of 4:250, treating it at 40°C for 120 minutes, taking it out, washing it with deionized water and acetone until the pH of the washing solution is 7, and finally treating it with a sodium hydroxide aqueous solution with a mass fraction of 40wt% at 80°C for 120 minutes, taking it out, and drying it to obtain pretreated aramid 1313 fiber; wherein the epichlorohydrin treatment solution is obtained by mixing epichlorohydrin and aluminum chloride at a mass ratio of 40:25;

[0057] A polyamino polymer is added to deionized water to form a polyamino polymer mixed solution with a concentration of 1.25 g / L, and the pretreated aramid 1313 fiber is added to the polyamino polymer mixed solution at a solid-liquid ratio of 1:50. After being treated at 80°C for 24 hours, the fiber is taken out, washed, and dried to obtain surface-modified aramid 1313 fiber; the surface-modified aramid 1313 fiber is added to a 0.2 mol / L silver nitrate aqueous solution at a solid-liquid ratio of 1:30, immersed for 60 minutes, and then treated with steam at 100°C for 30 minutes, washed, and dried to obtain modified aramid 1313 fiber.

[0058] Example 2

[0059] This embodiment discloses a method for preparing a modified aerogel, comprising the following steps:

[0060] Step B1, 12.9 g of ethanol, 29.9 g of a 37.5 wt% aqueous hydrochloric acid solution, and 1.1 g of vinyltrimethoxysilane were mixed, heated to reflux and stirred for reaction for 22 h, then the temperature of the mixed system was maintained at 70° C., 1.4 g of boric acid was added, stirred for reaction for 2.5 h, the temperature was raised to 83° C., and the stirring reaction was continued for 3.5 h to obtain boron-doped silane;

[0061] Step B2, cutting the hemp stems from which the bast has been stripped into 2 cm pieces, crushing, soaking in deionized water for 12 hours, and then stirring with a 1 mol / L sodium hydroxide aqueous solution at 75° C. for 3 hours, and finally stirring with a 2 wt % sodium hypochlorite aqueous solution at 65° C. for 3 hours, filtering, washing, and freeze-drying to obtain hemp fibers;

[0062] A chitosan / acetic acid solution with a mass fraction of 0.1wt% and a boron-doped silane aqueous solution with a mass fraction of 1wt% were mixed, hemp fibers were added, ultrasonic treatment was performed, and then freeze-dried at -78°C and ground to obtain an aerogel powder; wherein the mass ratio of the chitosan acetic acid solution, the boron-doped silane aqueous solution, and the hemp fibers was 100:4:0.004;

[0063] Step B3, adding 21 g of para-ester and 10.4 g of 4-mercaptobenzaldehyde to 550 g of dimethyl sulfoxide, ultrasonically treating at 42° C. for 50 min, then heating to 65° C. for reaction for 3.5 h, adding 16.2 g of DOPO, heating to 85° C. for further reaction for 4.5 h, cooling to room temperature, centrifuging, washing, and drying to obtain a flame retardant modifier;

[0064] 4 g of aerogel powder was added to 135 g of N,N-dimethylformamide, ultrasonically dispersed for 30 min, heated to 65 °C, and then 1.2 g of flame retardant modifier and 0.3 g of azobisisobutyronitrile were added. The mixture was stirred for 4 h. After the reaction was completed, it was centrifuged, washed and dried to obtain modified aerogel.

[0065] Example 3

[0066] This embodiment discloses a method for preparing a flame retardant and heat insulating layered composite fabric, comprising the following steps:

[0067] Step (1), in a nitrogen atmosphere, under a stirring condition of 150 r / min, mixing the cotton fiber with a sodium periodate aqueous solution with a concentration of 0.02 g / mL in a mass ratio of 1:40, reacting at 30° C. in the dark for 2.5 hours, filtering, ultrasonically washing with ethanol and deionized water three times in sequence, and drying to obtain pretreated cotton fiber;

[0068] 2.8 g of 2-amino-2-hydroxy-1,1'-binaphthalene was added to 80 g of methanol, and ultrasonic treatment was performed for 10 min to obtain a modified mixed solution; the pretreated cotton fiber and the modified mixed solution were mixed at a mass ratio of 1:40, reacted at 58° C. for 4 h, filtered, washed, and dried to obtain surface-modified cotton fiber;

[0069] Step (2), heating 5 g of coconut oil at 50° C. for 10 min to melt, then mixing with 5-10 g of a 1 wt % polyvinyl alcohol aqueous solution, stirring at a speed of 1400 r / min for 20 min, then adding dropwise 15 g of a 18.6 wt % ethyl cellulose / acetone solution at a speed of 1 mL / min, stirring at a speed of 800 r / min for 3 h at 32° C. to obtain phase change microcapsules;

[0070] The phase change microcapsules were added into deionized water, ultrasonically treated for 10 minutes, surface modified cotton fibers were added, stirred for 10 minutes, citric acid and sodium hypophosphite were added, heated to 95°C at a heating rate of 1.5°C / min and maintained for 150 minutes, filtered, washed, and dried to obtain modified cotton fibers; wherein the mass ratio of the phase change microcapsules, deionized water, surface modified cotton fibers, citric acid, and sodium hypophosphite was 2:300:10:6:6;

[0071] Step (3), soybean fiber, modified cotton fiber, and carbon fiber are mixed in a mass ratio of 25:56:1, blended into a yarn with an imperial count of 40S, and the yarn is used as warp and weft for weaving to obtain a yarn with a gram weight of 120 g / m 2 The inner fabric;

[0072] Modified aramid 1313 fiber, cotton fiber, and polytetrafluoroethylene fiber were mixed in a mass ratio of 30:20:30, and blended into a yarn with a British count of 40S, which was used as warp and weft for weaving to obtain a yarn with a gram weight of 140 g / m 2 Outer fabric;

[0073] Step (4), immersing the outer fabric in a modified aerogel treatment agent at a bath ratio of 1:15, taking it out after immersion treatment for 50 minutes, squeezing out excess water, and the squeezing rate is 80%, first drying at 60°C, and then baking at 140°C for 5 minutes, and finally rinsing with cold water, soaping, hot water washing, cold water washing and drying to obtain a functional outer fabric; wherein the modified aerogel treatment agent is made of 1% (owf = fabric weight) modified aerogel and 10g / L sodium carbonate aqueous solution;

[0074] One side of the functional outer fabric is coated with polyurethane adhesive at a coating amount of 18g / m 2The side of the functional outer fabric coated with the polyurethane adhesive is laminated to the inner fabric, and hot pressed for 40 seconds at a pressure of 0.15 MPa and a temperature of 100°C to obtain a flame-retardant and heat-insulating layered composite fabric.

[0075] Example 4

[0076] This embodiment discloses a method for preparing a flame retardant and heat insulating layered composite fabric, comprising the following steps:

[0077] Step (1), in a nitrogen atmosphere, under a stirring condition of 250 r / min, mixing the cotton fiber with a sodium periodate aqueous solution with a concentration of 0.02 g / mL in a mass ratio of 1:60, reacting at 40° C. in the dark for 1.5 hours, filtering, ultrasonically washing with ethanol and deionized water for 5 times in sequence, and drying to obtain pretreated cotton fiber;

[0078] 5.6 g of 2-amino-2-hydroxy-1,1'-binaphthalene was added to 100 g of methanol, and ultrasonic treatment was performed for 20 min to obtain a modified mixed solution; the pretreated cotton fiber and the modified mixed solution were mixed at a mass ratio of 1:60, reacted at 63° C. for 3 h, filtered, washed, and dried to obtain surface-modified cotton fiber;

[0079] Step (2), heating 10 g of coconut oil at 60° C. for 5 min to melt, then mixing with 5-10 g of a 1 wt % polyvinyl alcohol aqueous solution, stirring at a speed of 1600 r / min for 10 min, then adding dropwise 40 g of a 18.6 wt % ethyl cellulose / acetone solution at a speed of 1.5 mL / min, stirring at a speed of 1000 r / min for 2 h at 38° C. to obtain phase change microcapsules;

[0080] The phase change microcapsules were added into deionized water, ultrasonically treated for 20 minutes, surface modified cotton fibers were added, stirred for 20 minutes, citric acid and sodium hypophosphite were added, heated to 105°C at a heating rate of 2.5°C / min and maintained for 100 minutes, filtered, washed, and dried to obtain modified cotton fibers; wherein the mass ratio of the phase change microcapsules, deionized water, surface modified cotton fibers, citric acid, and sodium hypophosphite was 3:300:15:10:10;

[0081] Step (3), soybean fiber, modified cotton fiber, and carbon fiber are mixed in a mass ratio of 45:76:2, blended into a yarn with a British count of 60S, and the yarn is used as warp and weft for weaving to obtain a yarn with a gram weight of 140 g / m 2 The inner fabric;

[0082] Modified aramid 1313 fiber, cotton fiber, and polytetrafluoroethylene fiber were mixed in a mass ratio of 40:30:40, and blended into a yarn with a British count of 60S, which was used as warp and weft for weaving to obtain a yarn with a gram weight of 160g / m2 Outer fabric;

[0083] Step (4), immersing the outer fabric in a modified aerogel treatment agent at a bath ratio of 1:25, taking it out after immersion treatment for 100 minutes, squeezing out excess water, and the squeezing rate is 80%, first drying at 70°C, and then baking at 150°C for 5 minutes, and finally rinsing with cold water, soaping, hot water washing, cold water washing and drying to obtain a functional outer fabric; wherein the modified aerogel treatment agent is made of 3% (owf) modified aerogel and 10g / L sodium carbonate aqueous solution;

[0084] One side of the functionalized outer fabric is coated with polyurethane adhesive at a coating amount of 22 g / m 2 The side of the functional outer fabric coated with the polyurethane adhesive was laminated to the inner fabric, and hot pressed for 20 seconds at a pressure of 0.2 MPa and a temperature of 110°C to obtain a flame-retardant and heat-insulating layered composite fabric.

[0085] Example 5

[0086] This embodiment discloses a method for preparing a flame retardant and heat insulating layered composite fabric, comprising the following steps:

[0087] Step (1), in a nitrogen atmosphere, under a stirring condition of 200 r / min, mixing the cotton fiber with a sodium periodate aqueous solution with a concentration of 0.02 g / mL in a mass ratio of 1:50, reacting at 35° C. in the dark for 2 h, filtering, ultrasonically washing with ethanol and deionized water for 4 times in sequence, and drying to obtain pretreated cotton fiber;

[0088] 4.2 g of 2-amino-2-hydroxy-1,1'-binaphthalene was added to 90 g of methanol, and ultrasonic treatment was performed for 15 min to obtain a modified mixed solution; the pretreated cotton fiber and the modified mixed solution were mixed at a mass ratio of 1:50, reacted at 60° C. for 3.5 h, filtered, washed, and dried to obtain surface-modified cotton fiber;

[0089] Step (2), heating 7.5 g of coconut oil at 55° C. for 8 min to melt, then mixing with 5-10 g of a 1 wt % polyvinyl alcohol aqueous solution, stirring at a speed of 1500 r / min for 15 min, then adding dropwise 28 g of an 18.6 wt % ethyl cellulose / acetone solution at a speed of 1.2 mL / min, stirring at a speed of 900 r / min for 2.5 h at 35° C. to obtain phase change microcapsules;

[0090] The phase change microcapsules were added into deionized water, ultrasonically treated for 15 minutes, surface modified cotton fibers were added, stirred for 15 minutes, citric acid and sodium hypophosphite were added, heated to 100°C at a heating rate of 2°C / min and maintained for 120 minutes, filtered, washed, and dried to obtain modified cotton fibers; wherein the mass ratio of the phase change microcapsules, deionized water, surface modified cotton fibers, citric acid, and sodium hypophosphite was 2.5:300:12.5:8:8;

[0091] Step (3), soybean fiber, modified cotton fiber, and carbon fiber are mixed in a mass ratio of 35:66:1.5, blended into a yarn with an imperial count of 50S, and the yarn is used as warp and weft for weaving to obtain a yarn with a gram weight of 130 g / m 2 The inner fabric;

[0092] Modified aramid 1313 fiber, cotton fiber, and polytetrafluoroethylene fiber were mixed in a mass ratio of 35:25:35, and blended into a yarn with a British count of 50S, which was used as warp and weft for weaving to obtain a yarn with a gram weight of 150g / m 2 Outer fabric;

[0093] Step (4), immersing the outer fabric in a modified aerogel treatment agent at a bath ratio of 1:20, taking it out after immersion treatment for 80 minutes, squeezing out excess water, and the squeezing rate is 80%, first drying at 65°C, and then baking at 145°C for 4 minutes, and finally rinsing with cold water, soaping, hot water washing, cold water washing and drying to obtain a functional outer fabric; wherein the modified aerogel treatment agent is made of 2% (owf) modified aerogel and 10g / L sodium carbonate aqueous solution;

[0094] One side of the functionalized outer fabric is coated with polyurethane adhesive at a coating amount of 20 g / m 2 The side of the functional outer fabric coated with the polyurethane adhesive was laminated to the inner fabric, and hot pressed for 30 seconds at a pressure of 0.18 MPa and a temperature of 105°C to obtain a flame-retardant and heat-insulating layered composite fabric.

[0095] The modified aramid 1313 fiber and modified aerogel in the above Examples 3-5 are the modified aramid 1313 fiber prepared in Example 1 and the modified aerogel prepared in Example 2, respectively.

[0096] Comparative Example 1

[0097] Comparative Example 1 Compared with Example 2, in the process of preparing aerogel powder in Comparative Example 1, vinyltrimethoxysilane was used instead of boron-doped silane, and other conditions remained unchanged.

[0098] Comparative Example 2

[0099] Compared with Example 2, in the process of preparing aerogel powder in Comparative Example 2, no boron-doped silane was added. Therefore, the modified aerogel powder of this comparative example was obtained by simply mixing the aerogel powder and the flame retardant modifier, and other conditions remained unchanged.

[0100] Comparative Example 3

[0101] Comparative Example 3 Compared with Example 5, in the process of preparing the functionalized outer layer fabric in Comparative Example 3, the modified aerogel in the modified aerogel treating agent adopts the modified aerogel prepared in Comparative Example 1, and other conditions remain unchanged.

[0102] Comparative Example 4

[0103] Comparative Example 4 is compared with Example 5. In the process of preparing the functionalized outer fabric in Comparative Example 4, the modified aerogel in the modified aerogel treating agent adopts the modified aerogel prepared in Comparative Example 2, and other conditions remain unchanged.

[0104] Comparative Example 5

[0105] Comparative Example 5 Compared with Example 5, in the process of preparing the functionalized outer fabric, the modified aerogel in the modified aerogel treating agent is replaced with aerogel powder, and other conditions remain unchanged.

[0106] Comparative Example 6

[0107] Comparative Example 6 Compared with Example 5, in the process of preparing the functionalized outer fabric, the modified aerogel in the modified aerogel treating agent is replaced with a flame retardant modifier, and other conditions remain unchanged.

[0108] Comparative Example 7

[0109] Compared with Example 5, in Comparative Example 7, aramid 1313 fiber is used instead of modified aramid 1313 fiber during the preparation of the outer fabric, and other conditions remain unchanged.

[0110] Comparative Example 8

[0111] Comparative Example 8 Compared with Example 5, in the process of preparing the inner layer fabric in Comparative Example 8, surface modified cotton fiber is used instead of modified cotton fiber, and other conditions remain unchanged.

[0112] Comparative Example 9

[0113] Comparative Example 9 Compared with Example 5, in the process of preparing modified cotton fibers in Comparative Example 9, pretreated cotton fibers were used instead of surface-modified cotton fibers, and other conditions remained unchanged.

[0114] In the above embodiments and comparative examples, polyvinyl alcohol has a molecular weight of 61,000 g / mol and a brand of SigmaAldrich, which is from Beijing Bio Innovation Technology Co., Ltd.; the cotton fiber is Xinjiang long-staple cotton with a fiber length of 38-39 mm; the aramid 1313 fiber has a fineness of 2D and a fiber length of 30 mm, which is from DuPont of the United States; the polytetrafluoroethylene fiber has a specification of 1200D and is from Shanghai Fuding New Materials Technology Co., Ltd.; the soybean fiber has a length of 38 mm and is from Shanghai Guanqi Textile Co., Ltd.; the carbon fiber has a length of 5 mm and is purchased from Toray of Japan; the hemp stem (RHS) is obtained from a farmland; the polyurethane adhesive has a model of PU1179, a viscosity of 200 cP, an acidity of 7.0-9.0, and a solid content of 37±1%, which is from Anhui Zhongen Chemical Co., Ltd.

[0115] Experimental example

[0116] Test 1: Performance tests were performed on the flame retardant and heat insulating layered composite fabrics prepared in Examples 3-5 and Comparative Examples 3-9.

[0117] 1. Antibacterial performance test: According to GB / T 20944.3-2008 "Evaluation of antibacterial properties of textiles Part 3: Oscillation method", the antibacterial effects of each group of fabric samples on Escherichia coli and Staphylococcus aureus were tested after washing 50 times.

[0118] 2. Flame retardant performance test: The limiting oxygen index is determined according to GB / T5454 "Textile Combustion Performance Test-Oxygen Index Method"; the afterflaming time, smoldering time and damaged length are determined according to GB / T5455 "Textile Combustion Energy Test-Vertical Method".

[0119] 3. Thermal insulation performance test: Determine the Crowe value of the sample in accordance with the provisions of GB / T11048-2018 "Determination of thermal resistance and moisture resistance of textiles under steady-state conditions of physiological comfort (evaporative hot plate method)".

[0120] 4. Antistatic performance test: According to GB / T12703.2-2009 "Evaluation of electrostatic properties of textiles Part 2: Charge surface density", the antistatic properties of each group of fabric samples were tested after washing 50 times.

[0121] The test results are shown in Table 1:

[0122] Table 1

[0123]

[0124] It can be seen from the test results in Table 1 that the flame retardant and heat insulating layered composite fabrics prepared in Examples 3-5 of the present invention have excellent flame retardant and heat insulating properties, antibacterial properties and antistatic properties. From the comparison between Comparative Example 3 and Example 5, it can be seen that the boron element in the modified aerogel has a synergistic flame retardant effect with the nitrogen and phosphorus elements in the modified aerogel, thereby affecting the flame retardant properties of the composite fabric; from the comparison between Comparative Example 4 and Example 5, it can be seen that the addition of boron-doped silane in the modified aerogel, on the one hand, introduces flame retardant boron elements, and on the other hand, the carbon-carbon double bonds in silane contribute to the grafting of the flame retardant modifier on the aerogel, thereby affecting the grafting and dispersion of the aerogel on the cotton fibers in the outer fabric. Therefore, the addition of borosilicate helps to improve the flame retardant and heat insulating properties of the composite fabric; from the comparison between Comparative Example 5 and Example 5, it can be seen that the addition of the flame retardant modifier in the modified aerogel, on the one hand, introduces flame retardant nitrogen and phosphorus elements, and on the other hand, similar to Comparative Example 4, affects the grafting and dispersion of the aerogel on the outer layer. The grafting and dispersion on the cotton fibers in the material affect the flame retardant and heat insulating properties of the composite fabric; from the comparison between comparative example 6 and embodiment 5, it can be seen that due to the porous network structure of the aerogel powder and the presence of boron element therein, the flame retardant and heat insulating properties of the composite fabric can be improved; from the comparison between comparative example 7 and embodiment 5, it can be seen that the aramid 1313 fiber is modified to make the aramid 1313 fiber have antistatic and antibacterial properties, so that the composite fabric has lasting antistatic and antibacterial properties; from the comparison between comparative examples 8-9 and embodiment 5, it can be seen that after the cotton fiber is modified, a binaphthyl structure and a phase change microcapsule with heat insulation and cooling capabilities are introduced on its surface, which can better absorb the waste heat penetrating the fabric, thereby improving the heat insulating properties of the composite fabric.

[0125] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a flame retardant and heat insulating layered composite fabric, characterized in that: The following steps are involved: Step (1), the cotton fiber is treated with a sodium periodate aqueous solution and a modified mixed solution containing 2-amino-2-hydroxy-1,1'-binaphthalene in sequence to obtain a surface-modified cotton fiber; Step (2), using ethyl cellulose and coconut oil as raw materials to prepare phase change microcapsules; using citric acid as a crosslinking agent, connecting the phase change microcapsules to the surface modified cotton fibers to obtain modified cotton fibers; Step (3), blending soybean fiber, modified cotton fiber and carbon fiber into yarn, weaving to obtain inner layer fabric; blending modified aramid 1313 fiber, cotton fiber and polytetrafluoroethylene fiber into yarn, weaving to obtain outer layer fabric; The preparation method of modified aramid 1313 fiber comprises the following steps: Step A1, tetraethylenepentamine reacts with methyl acrylate to obtain a polyamino polymer; Step A2, pre-treating the aramid 1313 fiber to obtain the pre-treated aramid 1313 fiber; the pre-treated aramid 1313 fiber is treated with a polyamino polymer mixed solution, a silver nitrate aqueous solution, and steam to obtain a modified aramid 1313 fiber; Step (4), immersing the outer fabric in a modified aerogel treatment agent for infiltration treatment to obtain a functional outer fabric; coating one side of the functional outer fabric with a polyurethane adhesive, laminating it with the inner fabric, and hot pressing it to obtain a flame retardant and heat insulating layered composite fabric; The method for preparing the modified aerogel comprises the following steps: Step B1, boric acid reacts with vinyltrimethoxysilane to obtain boron-doped silane; para-ester, 4-mercaptobenzaldehyde, and DOPO react to obtain a flame retardant modifier; Step B2, extracting hemp fiber from hemp stems, and then cross-linking with chitosan and boron-doped silane to prepare aerogel powder; Step B3: modifying the aerogel powder with a flame retardant modifier to obtain modified aerogel.

2. The method for preparing the flame retardant and heat insulating layered composite fabric according to claim 1, characterized in that: In the step (1), the preparation method of the surface modified cotton fiber is: In a nitrogen atmosphere, under stirring conditions of 150-250 r / min, the cotton fiber is mixed with a sodium periodate aqueous solution having a concentration of 0.02 g / mL in a mass ratio of 1:(40-60), reacted at 30-40° C. in the dark for 1.5-2.5 h, filtered, washed, and dried to obtain pretreated cotton fiber; The pretreated cotton fiber and the modified mixed solution are mixed in a mass ratio of 1:(40-60), reacted at 58-63°C for 3-4 hours, filtered, washed, and dried to obtain surface-modified cotton fiber; wherein the modified mixed solution is obtained by mixing 2-amino-2-hydroxy-1,1'-binaphthalene and methanol in a mass ratio of (2.8-5.6):(80-100) and ultrasonically treating for 10-20 minutes.

3. The method for preparing the flame retardant and heat insulating layered composite fabric according to claim 1, characterized in that: In the step (2), the preparation method of the modified cotton fiber is: Heat the coconut oil at 50-60°C for 5-10 minutes to melt, then mix it with a 1wt% polyvinyl alcohol aqueous solution, stir it at a speed of 1400-1600r / min for 10-20min, then add a 18.6wt% ethyl cellulose / acetone solution dropwise at a speed of 1-1.5mL / min, and stir it at a speed of 800-1000r / min for 2-3h at 32-38°C to obtain phase change microcapsules; wherein the mass ratio of coconut oil, polyvinyl alcohol aqueous solution, and ethyl cellulose / acetone solution is (5-10):(5-10):(15-40); Phase change microcapsules are added to deionized water, ultrasonically treated for 10-20 minutes, surface modified cotton fibers are added, stirred for 10-20 minutes, citric acid and sodium hypophosphite are added, heated to 95-105°C at a heating rate of 1.5-2.5°C / min and maintained for 100-150 minutes, filtered, washed, and dried to obtain modified cotton fibers; wherein the mass ratio of phase change microcapsules, deionized water, surface modified cotton fibers, citric acid, and sodium hypophosphite is (2-3):300:(10-15):(6-10):(6-10).

4. The method for preparing the flame retardant and heat insulating layered composite fabric according to claim 1, characterized in that: In the step (3), the mass ratio of the soybean fiber, the modified cotton fiber and the carbon fiber is (25-45):(56-76):(1-2), the English count of the yarn blended from them is 40-60S, and the gram weight of the inner layer fabric is 120-140g / m 2 .

5. The method for preparing the flame retardant and heat insulating layered composite fabric according to claim 1, characterized in that: In the step (3), the mass ratio of the modified aramid 1313 fiber, the cotton fiber, and the polytetrafluoroethylene fiber is (30-40):(20-30):(30-40), the English count of the yarn blended from them is 40-60S, and the gram weight of the outer fabric is 140-160g / m 2 .

6. The method for preparing the flame retardant and heat insulating layered composite fabric according to claim 1, characterized in that: In the step (3), the method for preparing the modified aramid 1313 fiber comprises the following steps: Step A1, in a nitrogen atmosphere, tetraethylene pentamine is placed in an ice water bath, and a 34.2wt% methyl acrylate / methanol solution is added dropwise at a rate of 0.8-1.2mL / min under stirring conditions. After the addition is completed, stirring is continued at room temperature for 3.5-4.5h, the temperature is raised to 145-155°C, and the mixture is allowed to stand for 3.5-4.5h to obtain a polyamino polymer; wherein the amount ratio of tetraethylene pentamine to methyl acrylate / methanol solution is (4.7-9.4)g:(7-14)mL; Step A2, adding the washed aramid 1313 fiber to dichloromethane at a solid-liquid ratio of 4:(220-280), taking out after ultrasonic treatment for 20-40 minutes, then adding it to an epichlorohydrin treatment solution at a solid-liquid ratio of 4:(240-260), treating it at 38-42° C. for 100-150 minutes, taking it out, washing it with deionized water and acetone until the pH of the washing solution is 7, finally treating it with a sodium hydroxide aqueous solution with a mass fraction of 30-50wt% at 75-85° C. for 100-150 minutes, taking it out, and drying it to obtain pretreated aramid 1313 fiber; wherein the epichlorohydrin treatment solution is obtained by mixing epichlorohydrin and aluminum chloride at a mass ratio of 40:25; A polyamino polymer is added to deionized water to form a polyamino polymer mixed solution with a concentration of 0.5-2 g / L, and the pretreated aramid 1313 fiber is added to the polyamino polymer mixed solution at a solid-liquid ratio of 1: (40-60), and the pretreated aramid 1313 fiber is treated at 75-85° C. for 22-26 hours, then taken out, washed, and dried to obtain surface-modified aramid 1313 fiber; the surface-modified aramid 1313 fiber is added to a silver nitrate aqueous solution with a concentration of 0.1-0.3 mol / L at a solid-liquid ratio of 1: (25-35), and immersed for 50-70 minutes, and then treated with steam at 100° C. for 20-40 minutes, washed, and dried to obtain modified aramid 1313 fiber.

7. The method for preparing the flame retardant and heat insulating layered composite fabric according to claim 1, characterized in that: In the step (4), the modified aerogel treatment agent is made of 1-3% (owf) modified aerogel and 10g / L sodium carbonate aqueous solution; the infiltration treatment conditions are: the bath ratio of the outer fabric to the modified aerogel treatment agent is 1: (15-25), and the infiltration treatment time is 50-100min; the rolling rate is 80%, first drying at 60-70°C, and then baking at 140-150°C for 3-5min.

8. The method for preparing the flame retardant and heat insulating layered composite fabric according to claim 1, characterized in that: In the step (4), the coating amount of the polyurethane adhesive is 18-22 g / m 2 ; Hot pressing conditions: hot pressing for 20-40s at a pressure of 0.15-0.2MPa and a temperature of 100-110°C.

9. The method for preparing the flame retardant and heat insulating layered composite fabric according to claim 1, characterized in that: In the step (4), the method for preparing the modified aerogel comprises the following steps: Step B1, ethanol, a 37.5wt% hydrochloric acid aqueous solution, and vinyltrimethoxysilane are mixed, heated to reflux and stirred for reaction for 20-24h, and then the temperature of the mixed system is maintained at 65-75°C, and then boric acid is added, stirred for reaction for 2-3h, the temperature is raised to 80-85°C, and the stirring reaction is continued for 3-4h to obtain boron-doped silane; wherein the mass ratio of ethanol, hydrochloric acid aqueous solution, vinyltrimethoxysilane, and boric acid is (8.6-17.2):(19.9-39.8):(0.7-1.4):(0.9-1.8); Step B2, cutting the hemp stems from which the bast has been stripped into pieces of 1-4 cm, crushing, soaking in deionized water for 10-15 hours, and then stirring with a 1 mol / L sodium hydroxide aqueous solution at 70-80° C. for 2-4 hours, and finally stirring with a 2 wt % sodium hypochlorite aqueous solution at 60-70° C. for 2-4 hours, filtering, washing, and freeze-drying to obtain hemp fibers; A chitosan / acetic acid solution with a mass fraction of 0.1wt% and a boron-doped silane aqueous solution with a mass fraction of 1wt% are mixed, hemp fiber is added, ultrasonic treatment is performed, and then freeze-dried at (-80)-(-75)°C and ground to obtain an aerogel powder; wherein the mass ratio of the chitosan acetic acid solution, the boron-doped silane aqueous solution, and the hemp fiber is 100:(2-6):(0.003-0.005); Step B3, adding the para-ester and 4-mercaptobenzaldehyde to dimethyl sulfoxide, ultrasonically treating at 40-45°C for 40-60min, then heating to 60-70°C for reaction for 3-4h, adding DOPO, heating to 80-90°C for further reaction for 4-5h, cooling to room temperature, centrifuging, washing, and drying to obtain a flame retardant modifier; wherein the mass ratio of the para-ester, 4-mercaptobenzaldehyde, dimethyl sulfoxide, and DOPO is (14-28):(6.9-13.8):(500-600):(10.8-21.6); The aerogel powder is added to N,N-dimethylformamide, ultrasonically dispersed for 20-40 minutes, heated to 50-80°C, and then a flame retardant modifier and azobisisobutyronitrile are added, stirred for reaction for 3-5 hours, and after the reaction is completed, centrifuged, washed, and dried to obtain a modified aerogel; wherein the mass ratio of aerogel powder, N,N-dimethylformamide, flame retardant modifier, and azobisisobutyronitrile is (3-5):(120-150):(1-1.5):(0.2-0.3).

10. A flame retardant and heat insulating layered composite fabric prepared by the method for preparing a flame retardant and heat insulating layered composite fabric as claimed in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Flame-retardant polyester fabric and preparation method thereof

    CN116353159A

  • Method for preparing silver-texture golden regenerated cellulose fabric

    CN104928916A

  • Method for generating antibacterial cotton fibers in situ

    CN105040417A

  • Finishing method of antibacterial cotton fabric

    CN105040436A

Cited By

  • Low-carbon renewable fabric based on modified soybean protein fibers as well as preparation method and application of low-carbon renewable fabric

    CN119820930A

  • A low-carbon renewable fabric based on modified soybean protein fiber and a preparation method and application thereof

    CN119820930B